At Home: Family reintegration of trafficked Indonesian men - Surtees, Rebecca (Anti-Trafficking Review, 2018)
Large numbers of Indonesian men migrate each year for work in construction, in factories and in agriculture, on plantations and on fishing boats. Many of them end up exploited in ways that constitute human trafficking, suffering violence, deprivation, restricted freedom and severe exploitation as well as long periods of separation from their families. This article explores the challenges faced by forty-nine Indonesian men reintegrating into their families and communities after having been trafficked. While many problems with the family were caused by economics, tensions also resulted from long separations, fractured relationships, and frustration and blame over ‘failed’ migration and unfulfilled expectations. Tensions were sometimes exacerbated when men faced recrimination and blame in their communities after return. Understanding the nature of and reasons for the problems that men faced after trafficking is vital in considering how trafficked men and their families can be supported to recover and reintegrate after trafficking.